Modified Rankin Scale at 90 Days Versus National Institutes of Health Stroke Scale at 24 Hours as Primary Outcome in Acute Stroke Trials - Johanna M. Ospel; Scott Brown; Salome Bosshart; Alexander Stebner; Kazutaka Uchida; Andrew Demchuk; Jeffrey L. Saver; Philip White; Keith W. Muir; Diederik W. J. Dippel; Charles B. L. M. Majoie; Tudor G. Jovin; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background We investigate whether the National Institutes of Health Stroke Scale (NIHSS) at 24 hours could serve as a primary outcome in acute ischemic stroke trials, and whether combining 90‐day modified Rankin Scale (mRS) and 24‐hour NIHSS in a hierarchical outcome could enhance detection of treatment effect, using endovascular treatment (EVT) as an exemplary study intervention. Methods This was a post hoc analysis of pooled data from 7 randomized EVT trials. Twenty‐four‐hour NIHSS as a surrogate outcome for 90‐day mRS was assessed in a causal mediation model. A 7‐point ordinal NIHSS score was generated by grouping 24‐hour NIHSS, including death as a separate category (“ordinal” NIHSS). EVT effect sizes and sample sizes required for detecting EVT benefit with 80% power were compared when using granular 24‐hour NIHSS, ordinal 24‐hour NIHSS, 90‐day mRS, and a hierarchical outcome (win ratio) that combines 90‐day mRS and 24‐hour NIHSS. Results A total of 1720 patients were included. Twenty‐four‐hour NIHSS mediated the association between EVT and 90‐day mRS and met criteria for a useful surrogate outcome. Effect sizes were highest and sample sizes required to detect EVT benefit smallest for the win ratio approach (228), followed by 90‐day mRS (240) and ordinal 24‐hour NIHSS (242). In patients with baseline NIHSS <10 and ≥25, ordinal 24‐hour NIHSS resulted in the highest effect size. Conclusions Twenty‐four‐hour NIHSS is a useful surrogate outcome for 90‐day mRS in patients with acute ischemic stroke undergoing EVT, with a similar EVT effect size compared with 90‐day mRS. It could potentially enhance detection of EVT benefit in patients with very low or high baseline NIHSS. An ordered hierarchical outcome could improve detection of EVT treatment effect.